Acetyl- and O-alkyl- derivatives of β-mangostin from Garcinia mangostana and their anti-inflammatory activities. Issue 12 (18th June 2018) - Karunakaran, Thiruventhan; Ee, Gwendoline Cheng Lian; Ismail, Intan Safinar; Mohd Nor, Siti Mariam; Zamakshshari, Nor Hisam
Abstract: Pure β-mangostin (1) was isolated from the stem bark of Garcinia mangostana L. One monoacetate (2 ) and five O -alkylated β-mangostin derivatives (3–7 ) were synthesised from β-mangostin. The structures of these compounds were elucidated and determined using spectroscopic techniques such as 1D NMR and MS. The cytotoxicities and anti-inflammatory activities of these five compounds against RAW cell 264.7 were tested. The structural-activity relationship studies indicated that β-mangostin showed a significant activity against the LPS-induced RAW cell 264.7, while the acetyl- as well as the O -alkyl- β-mangostin derivatives did not give good activity. Naturally occurring β-mangostin demonstrated comparatively better anti-inflammatory activity than its synthetic counterparts. Abstract :